Uterine Tumor Resembling Ovarian Sex Cord Tumor (UTROSCT) Commonly Exhibits Positivity With Sex Cord Markers FOXL2 and SF-1 but Lacks FOXL2 and DICER1 Mutations. (July 2016) - Croce, Sabrina; de Kock, Leanne; Boshari, Talia; Hostein, Isabelle; Velasco, Valerie; Foulkes, William D.; McCluggage, W. Glenn
Abstract : Uterine tumor resembling ovarian sex cord tumor (UTROSCT) is a rare neoplasm which morphologically and immunohistochemically exhibits overlap with an ovarian sex cord tumor. Although many of these neoplasms are positive with markers of ovarian sex cord-stromal tumors, staining is often limited and the pathogenesis of UTROSCT is unknown. To further explore the sex cord lineage of UTROSCT, we studied 19 of these neoplasms and examined the expression of 2 recently described markers of ovarian sex cord-stromal tumors, FOXL2, and steroidogenic factor-1. We also undertook FOXL2 and DICER1 mutation analysis in these cases; a somatic missense mutation in codon C134W (402C→G) of FOXL2 gene has been demonstrated in the vast majority (>95%) of ovarian adult granulosa cell tumors and somatic DICER1 mutations are found in approximately 60% of ovarian Sertoli-Leydig cell tumors. Ten of 19 cases (53%) exhibited nuclear immunoreactivity with FOXL2 and 11 of 19 (58%) exhibited nuclear staining with steroidogenic factor-1. Neither FOXL2 nor DICER1 mutations were identified in any case where there was sufficient tumor tissue for analysis (18 and 9 cases, respectively). Despite exhibiting an immunophenotype characteristic of a sex cord-stromal tumor, mutations in FOXL2 and DICER1, the 2 most common mutations hitherto reported in ovarian sex cord-stromal tumors, are not a feature of UTROSCT.